Managerial Accounting / Sixth Edition - Dominiak Geraldine F; Louderback Joseph G. (Pws-Kent Publishing Company, 1991)
Introduction, Volume-Cost-Profit Analysis and Decision Making, Profit Planning, Analyzing Cost Behavior, Additional Aspects of Volume-Cost-Profit Analysis, Short-Term Decisions and Accounting Information, Budgeting, Operational Budgeting, Financial Budgeting, Capital Budgeting, Control and Performance Evaluation, Responsibility Accounting, Divisional Performance Measurement, Control and Evaluation of Cost Centers, Product Costing, Introduction to Product Costing: Job-Order Costing, Standard Costing: Absorption and Variable, Process Costing and the Cost Accounting Cycle, Special Topics, Quantitative Methods and Managerial Accounting, Statement of Cash Flows, Analyzing Financial Statements, Appendix: Time Value of Money, Index.
Introduction, Volume-Cost-Profit Analysis and Decision Making, Profit Planning, Analyzing Cost Behavior, Additional Aspects of Volume-Cost-Profit Analysis, Short-Term Decisions and Accounting Information, Budgeting, Operational Budgeting, Financial Budgeting, Capital Budgeting, Control and Performance Evaluation, Responsibility Accounting, Divisional Performance Measurement, Control and Evaluation of Cost Centers, Product Costing, Introduction to Product Costing: Job-Order Costing, Standard Costing: Absorption and Variable, Process Costing and the Cost Accounting Cycle, Special Topics, Quantitative Methods and Managerial Accounting, Statement of Cash Flows, Analyzing Financial Statements, Appendix: Time Value of Money, Index.